Inverse Opal Photonic Crystals as a Strategy to Improve Photocatalysis: Underexplored Questions - Curti, Mariano (2015)
The structuring of materials in the form of photonic crystals for photocatalytic applications is a quite new strategy aiming to enhance the performance of the photocatalysts at wavelength ranges where their absorption is poor. It is of particular interest to successfully manufacture an efficient photocatalytic system that could make use of solar light. Thus, the key of the strategy is the "slow photon effect", occurring at the edges of a forbidden band for photons. In this Perspective we have chosen some questions that we consider of relevance and that are well worth being addressed both theoretically and experimentally. It is the aim of this discussion to eventually lead to a more productive use of inverse opals as photonic photocatalytic materials.